2003
DOI: 10.1097/00002060-200308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Noninvasive positive-pressure ventilation provides a long-lasting benefit on symptoms and quality of life indicators for amyotrophic lateral sclerosis patients and should be offered to all patients with symptoms of sleep disordered breathing or inspiratory muscle dysfunction. It can also prolong tracheostomy-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2 The positive effect on blood-gas parameters, quality of life, and hypercapnia-associated symptoms was reproduced convincingly in several subsequent studies. Polysomnographic studies showed an improvement of oxygen saturation, pCO 2 , and apnea-hypopnea-index, 8,9 leading to reduced daytime fatigue and depression, 10 as well as improved sleep and quality of life. 9,11 Patients may notice improvements already after the first night of NIV usage, 8 and continued therapy promises long-lasting positive effects over several months, 10,12 although they weaken over time.…”
Section: Effects On Survival and Quality Of Lifementioning
confidence: 96%
“…2 The positive effect on blood-gas parameters, quality of life, and hypercapnia-associated symptoms was reproduced convincingly in several subsequent studies. Polysomnographic studies showed an improvement of oxygen saturation, pCO 2 , and apnea-hypopnea-index, 8,9 leading to reduced daytime fatigue and depression, 10 as well as improved sleep and quality of life. 9,11 Patients may notice improvements already after the first night of NIV usage, 8 and continued therapy promises long-lasting positive effects over several months, 10,12 although they weaken over time.…”
Section: Effects On Survival and Quality Of Lifementioning
confidence: 96%
“…NIV also improves blood gas parameters and respiratory symptoms. Recent polysomnographic studies have demonstrated improvement of oxygen saturation, apnea–hypopnea index, and transcutaneous carbon dioxide tension, 50 and also an improvement of sleep quality, daytime fatigue, depression, 51 and quality of life. 52 Although direct correlations between respiratory symptoms and blood gas parameters have not been reported in the aforementioned studies, improvement of blood gas parameters and quality of life indicators both remained stable over an observation period of 10 months.…”
Section: Noninvasive Ventilationmentioning
confidence: 99%
“… 52 Although direct correlations between respiratory symptoms and blood gas parameters have not been reported in the aforementioned studies, improvement of blood gas parameters and quality of life indicators both remained stable over an observation period of 10 months. 51 …”
Section: Noninvasive Ventilationmentioning
confidence: 99%
“…NIV may be considered at the earliest sign of nocturnal hypoventilation or respiratory insufficiency in order to improve compliance (Level C) (23 Miller, 28 Pinto, 29 Aboussouan). Orthopnea has been shown to be a strong predictor of benefit and also better compliance with NIV (24 Bourke).…”
Section: Respiratory Insufficiencymentioning
confidence: 99%